CMOS charge qubits and qudits: entanglement entropy and mutual information as an optimization method to construct CNOT and SWAP Gates. (30th July 2021) - Giounanlis, Panagiotis; Wu, Xutong; Sokolov, Andrii; Petropoulos, Nikolaos; Koskin, Eugene; Bashir, Imran; Leipold, Dirk; Staszewski, Robert Bogdan; Blokhina, Elena
Abstract: In this paper, we propose an optimization method for the construction of two-qubit and two-qudit quantum gates based on semiconductor position-based charge qubits. To describe the evolution of various quantum states, we use a Hubbard based model and Lindblad formalism. The suggested optimization algorithm uses the time evolution of entanglement entropy and mutual information for the determination of the system parameters to achieve high fidelity gates.